AERODYNAMIC CHARACTERISTICS OF “FAN-IN-FIN” SYSTEM IN CONDITION OF FLOWING UNDER ZERO ATTACK ANGLE - V. I. Shaydakov (Научный вестник МГТУ ГА)
Fan-in-fin system can be used as single-rotor helicopter fenestrons propulsion system of low-speed airplanes and dirigibles as well as vehicles with remote control.The article suggests way to continue the author’s research in the field of fan-in-fin system aerodynamics.It also offers a method of aerodynamic characteristics of “fan-in-fin” (fenestron) system with cylindrical diffuser of limited length in flow regime under zero angle of attack calculation. The article gives some formula to calculate the flow velocity through the disk area which decrease with the increase of the defusser and air speed.Correlation between fan thrust power and ring thrust on these regimes and momentum drag are found. Momentum drag is high enough, this fact leads to back deviation of total aerodynamic force system. This angle increases with increase of the diffuser length and at medium speed it can reach 30°.Certainty of suggested algorithms is proved by comparison with experiments for helicopter fenestron and unmanned air vehicle by tests in wind tunnel of MAI.